(untitled) (Canadian Journal of Native Studies, 2026)
Abstract The aim of this article is to provide second language teachers and course designers working with Indigenous learners with elements of theories and practices that best suit their learners needs. In order to do that, two reviews of literature are presented: the first one deals with Eurocentric second language didactics paradigm in use today and the second one deals with traditional Indigenous education principles and techniques. A conceptual frame of second language teaching to Indigenous learners is then provided and practical suggestions are given to teachers and course designers working with this clientele.